Analisa Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Otomotif dan Komponennya yang Terdaftar Di BEI Periode 2015-2019 - Ainul Habib; R. Gatot Heru Pranjoto (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Return On Equity, Total Assets Turnover, and Firm Size on firm value (PBV), sim ultaneously or partially on autom otive com panies and their components listed on the IDX for the 2015-2019 period. The results showed that simultaneously all independent variables had a significant effect on firm value. Current Ratio has an insignificant positive effect on firm value, Debt to Equity Ratio has a non-significant positive effect on firm value, Return On Equity has a significant positive effect on firm value, Total Assets Turnover has an insignificant positive effect on firm value, and Firm Size has an insignificant positive effect on firm value.